The moving finger - Christie, Agatha (HarperCollins London, 2005)
A facsimile first edition hardback of the Miss Marple books, published to mark the 75th anniversary of her first appearance and to celebrate her new-found success on television. When The Murder at the Vicarage was published in October 1930, little did the literary world realise that Agatha Christie, already famous for her early Poirot titles, was introducing a character who would become the best-loved female sleuth of all time. The 14 Marple books would appear at intervals over the next 49 years, with Miss Marple's Final Cases published in 1979, three years after Agatha's death. To mark the 75th anniversary of Miss Marple's first appearance, and to celebrate her renewed fortunes as a primetime television star, this collection of facsimile first editions will be the perfect way to enjoy these books in their original form - 12 novels and two short story collections. Reproducing the original typesetting and formats from the first editions from the Christie family's own archive copies, these books sport the original covers which have been painstakingly restored from the best available copies, reflecting five decades of iconic cover design